2013
DOI: 10.1016/j.jcin.2012.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection

Abstract: Nonatherosclerotic SCAD predominantly affects women, and most have concomitant FMD. We suspect these patients have underlying coronary FMD that predisposed them to SCAD, but this requires proof from histology or intracoronary imaging of the affected coronary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 349 publications
(153 citation statements)
references
References 27 publications
2
145
2
4
Order By: Relevance
“…However, our recent discovery of a dominant association between SCAD and extracoronary FMD strongly suggested that underlying coronary involvement with FMD predisposed these patients to dissection of their coronary arteries. [8][9][10] Furthermore, this high frequency of association also implied that coronary FMD was more frequent than previously believed. However, the angiographic diagnosis of CFMD had been elusive, Figure 5.…”
Section: Dilatationmentioning
confidence: 50%
See 1 more Smart Citation
“…However, our recent discovery of a dominant association between SCAD and extracoronary FMD strongly suggested that underlying coronary involvement with FMD predisposed these patients to dissection of their coronary arteries. [8][9][10] Furthermore, this high frequency of association also implied that coronary FMD was more frequent than previously believed. However, the angiographic diagnosis of CFMD had been elusive, Figure 5.…”
Section: Dilatationmentioning
confidence: 50%
“…8 Subsequently, in our larger SCAD cohort that was prospectively followed up, we found FMD to be present in 72% to 86% of patients with SCAD routinely screened for FMD in multiple vascular territories. 9,10 Given that SCAD and FMD are deemed relatively rare, this strong association implicates causality of SCAD owing to underlying coronary FMD (CFMD). This mechanism is plausible because arteries affected by FMD are structurally weakened and prone to dissection.…”
Section: Clinical Perspective On P 1559mentioning
confidence: 99%
“…33 More recently, a frequent association between SCAD and FMD of extracoronary vessels has been demonstrated in several single-center patient series, with prevalence varying from 52% to 86%. [33][34][35][36][37] The largest and best explored series included 168 patients with SCAD, of which 72% had FMD of the renal, iliac, or cerebrovascular arteries. 33 In an earlier series of 50 patients published by the same group, lesions of ≥2 noncoronary vascular beds were found in 42% of patients.…”
Section: Spontaneous Coronary Artery Dissection and Fmdmentioning
confidence: 99%
“…However, a recent contemporary review suspect that the true prevalence in patients presenting with ACS might be as high as 1.7–4% on the basis of moderate series [4,5]. SCAD affects women in more than 90% of the cases, and with the exclusion of the atherosclerotic cases, women constitute up to 95% of the cases [4,68]. In men, however, the atherosclerotic entity is more prevalent [9].…”
Section: Discussionmentioning
confidence: 99%
“…Potential predisposing factors include fibromuscular dysplasia (FMD), postpartum status, multiparty, connective tissue disorders, and hormonal therapy [68,10]. Precipitating stressors such as intense exercise or emotional stress, labour and delivery, intense Valsalva-type activities, or recreational drug uses were reported as a provoking factor of the acute coronary event in over 50 percent of cases in a contemporary series [6]. Of note, our patient has no risk factor for atherosclerosis nor any predisposing factor.…”
Section: Discussionmentioning
confidence: 99%